2022
DOI: 10.1038/s43705-022-00207-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the membrane lipid composition of a Sulfurimonas species depend on the electron acceptor used for sulfur oxidation

Abstract: Sulfurimonas species are among the most abundant sulfur-oxidizing bacteria in the marine environment. They are capable of using different electron acceptors, this metabolic flexibility is favorable for their niche adaptation in redoxclines. When oxygen is depleted, most Sulfurimonas spp. (e.g., Sulfurimonas gotlandica) use nitrate ($${{{{{{{\mathrm{NO}}}}}}}}_3^ -$$ NO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…On the other hand, factors such as the nature of electron donors or acceptors (e.g., soluble vs. insoluble or charged vs. uncharged) may impose an opposing biosynthetic pressure to maintain a lower degree of cyclization. A recent study reported changes in bacterial lipid composition as a function of electron acceptor (nitrate vs. manganese dioxide), and the changes were attributed to the differences in the electron transport chains (ETC) embedded in the cell membrane ( 42 ). For archaeal lipids, changes in the membrane composition in response to the extent of anaerobiosis (e.g., S 0 vs. O 2 as the electron acceptor) have been observed ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, factors such as the nature of electron donors or acceptors (e.g., soluble vs. insoluble or charged vs. uncharged) may impose an opposing biosynthetic pressure to maintain a lower degree of cyclization. A recent study reported changes in bacterial lipid composition as a function of electron acceptor (nitrate vs. manganese dioxide), and the changes were attributed to the differences in the electron transport chains (ETC) embedded in the cell membrane ( 42 ). For archaeal lipids, changes in the membrane composition in response to the extent of anaerobiosis (e.g., S 0 vs. O 2 as the electron acceptor) have been observed ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the relative peak areas calculated abundance do not indicate the actual relative abundance of different lipids in samples. Nevertheless, this method allowed comparison of lipids between different cultures or cultivation conditions, rather than determining the absolute quantities of each lipid present 82 .…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the relative peak areas do not necessarily indicate the actual relative abundance of different lipids. Nevertheless, this method allowed comparison between different cultivation conditions ( 73 ).…”
Section: Methodsmentioning
confidence: 99%